An overview of the Ministry of Higher Education (MOHE) research grants application: UNIMAS Innovation/ Nor Atikah Junaidi - Junaidi, Nor Atikah (2016)
This chapter contains of eight (8) sections. Section 1.2 Backgrounds of UNIMAS INNOVATION. While, section 1.3 explains Vision of UNIMAS INNOVATION. Next section 1.4 explains Mission of UNIMAS INNOVATION. Section 1.5 showed Organizational Structures. Section 1.6 explains Service Provided and section 1.7 showed the Department Logo’s and lastly in Section 1.8 explains the chapter summary. UNIMAS INNOVATION, which was first known as Research and Innovation Management Centre (RIMC), was established in April 2003. As UNIMAS grew in size and stature, the need to strengthen research and grants within UNIMAS gave birth to Research and Innovation Management Centre (RIMC) on 10 January 2005.